Residents’ Perceived Impact of COVID-19 on Saudi Ophthalmology Training Programs-A Survey - Alahmadi AS (Dove Medical Press, 2020)
Adel Salah Alahmadi,1,2 Hatlan M Alhatlan,3 Halah Bin Helayel,4 Rajiv Khandekar,4 Ahmed Al Habash,5 Sami Al-Shahwan6,7 1Vitreoretinal Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Department of Ophthalmology, MOH, Madinah, Saudi Arabia; 3Department of Ophthalmology, King Fahad Hospital, MOH, Hofuf, Saudi Arabia; 4Research Department, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 5Department of Ophthalmology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 6Glaucoma Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 7Residency and Fellowship Office, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Ahmed Al HabashDepartment of Ophthalmology, Imam Abdulrahman Bin Faisal University, King Fahd Hospital of the University, King Faisal Road, Dammam 31952, Saudi ArabiaTel +966 138966666 Ext 1323Fax +966 138966770Email ahmedalhabash@gmail.comPurpose: To evaluate the impact of the current pandemic on ophthalmology residency training in Saudi Arabia, focusing on its effects on clinical education, training, and the mental well-being of the trainees.Methods: An online self-administered questionnaire was distributed among residents in the Saudi ophthalmology training programs between July 7 and 14, 2020. In this study, we explored residents’ opinions regarding training disruption and virtual education. The patient health questionnaire (PHQ-9) was used to assess the COVID-19 pandemic’s impact on their mental health. We used descriptive statistics for data analysis.Results: Out of 183 registered ophthalmology residents, 142 participated in this study. Ninety-six participants (35.4%) were rotated at a specialized eye hospital during the COVID-19 pandemic, while 52 (19.2%) had rotations in the ophthalmology department at general hospitals. Those who rotated in both types of hospitals were 123 (45.4%). According to the participants, there was a significant decline in exposure to surgical and office-based procedures compared to emergency eye consultations (Friedman P < 0.001). The COVID-19 pandemic’s effect on mental health was reported by 100 (70.5%) participants. Eighty-five (55.4%) respondents were satisfied with the virtual method of education.Conclusion: COVID-19 pandemic has disrupted residents’ clinical and surgical training in the Saudi ophthalmology training programs. Additionally, we believe that COVID-19 may have a negative impact on trainees’ mental health. Fortunately, the current pandemic provided an innovative education method that will likely be used even after the pandemic.Keywords: ophthalmology training, curriculum, outbreak, mental health, Saudi Arabia, Residency training program, COVID-19, medical education